Perancangan dan Implementasi Self Assessment Untuk Sertifikasi ISO 9001:2015 Menggunakan Metode Baldrige Scoring - Hardwinto Rantung; Benedictus Rahardjo (Jurnal Titra, 2018)
Company X is a service company in plating. This aim of this research is designing a self assessment checklist associate with interest requirement of quality management of ISO 9001:2015 in Company X. Company X has implemented ISO 9001:2015, however this company never did the audit internal. To do the audit internal, company X need a self assessment checklist to help each department and to know the lack. This research was designed a self assessment checklist based on the requirement of clause 4 until clause 10 which exist on quality management system of ISO 9001:2015. On a self assessment checklist, the scoring category is using the modification from Baldrige scoring on process dimension and result dimension. Based on this application of a self assessment checklist, obtained the percentage from clause 4 until clause 10. This are the percentage 68,57%, 80%, 64,44%, 80%, 71,6%, 82,67%, 55,56%.